2022
DOI: 10.3390/cancers14163846
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Low Density Neutrophils Are Associated with Resistance to First Line Anti-PD1/PDL1 Immunotherapy in Non-Small Cell Lung Cancer

Abstract: Single-agent immunotherapy has been widely accepted as frontline treatment for advanced non-small cell lung cancer (NSCLC) with high tumor PD-L1 expression, but most patients do not respond and the mechanisms of resistance are not well known. Several works have highlighted the immunosuppressive activities of myeloid subpopulations, including low-density neutrophils (LDNs), although the context in which these cells play their role is not well defined. We prospectively monitored LDNs in peripheral blood from pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
4
23
0
Order By: Relevance
“…Finally, we confirmed that the cancer patients in our cohort showed elevated percentages of circulating neutrophils, which is a signature of dysfunctionality and elevated baseline inflammation as previously shown by us [ 43 , 46 , 47 ]. This could explain the exacerbated Th17 responses after vaccination and/or SARS-CoV-2 infection in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, we confirmed that the cancer patients in our cohort showed elevated percentages of circulating neutrophils, which is a signature of dysfunctionality and elevated baseline inflammation as previously shown by us [ 43 , 46 , 47 ]. This could explain the exacerbated Th17 responses after vaccination and/or SARS-CoV-2 infection in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…We previously showed in lung cancer patients that myeloid profiles enriched in granulocytes contribute to dysfunctional immunity and treatment failure [ 43 , 44 , 45 , 46 ]. Therefore, we evaluated whether cancer patients in our cohort showed dysfunctional myeloid profiles that could explain accentuated inflammatory responses to COVID-19 and mRNA vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, PD-L1/PD-1 blockade is carried out systemically and will have a broad impact in the immune system. These global effects will probably contribute to clinical responses, and systemic immune biomarkers could be an inexpensive way forward for their clinical use [ 19 , 29 , 45 , 48 , 50 , 57 , 144 , 174 , 175 ]. Therefore, immune profiling of immune cells in peripheral blood samples could be a promising non-invasive procedure to evaluate biomarkers of response in immunotherapies.…”
Section: Systemic Cd4 Immunity As a Biomarker Of Response To Pd-l1/pd...mentioning
confidence: 99%
“…To achieve this, high-dimensional techniques, such as multiparametric flow cytometry, can provide more accurate quantification of different cell types, leading to better correlations with clinical outcomes. Using these techniques, the prognostic value of cell populations such as monocytes, neutrophils and other granulocytes have been confirmed in NSCLC patients undergoing PD-L1/PD-1 blockade immunotherapies [ 45 , 174 ].…”
Section: Systemic Cd4 Immunity As a Biomarker Of Response To Pd-l1/pd...mentioning
confidence: 99%
“…Furthermore, compared with NDNs, LDNs express higher levels of PD-L1 and can inhibit cytotoxic T cells and natural killer (NK) cells [ 49 , 82 ]. In a recent study, Arasanz et al showed a possible role of circulating LDNs in the development of resistance to PD-1/PDL1 immunotherapy in non-small-cell lung cancer (NSCLC) patients [ 83 ]. In breast cancer patients, LDN levels were associated with a worse prognosis and were significantly higher in the case of metastatic cancer than in non-metastatic cases [ 77 ].…”
Section: Neutrophil Heterogeneity In Cancer: N1/n2 Ndn/ldn and G-mdscmentioning
confidence: 99%